Computer aided teaching unpacked: exploring into methods of using the computer as a teaching tool for Ordinary Level students: A case study of Secondary Schools in Shurugwi Urban Cluster. - Madhovi, Terrance (Midlands State University, 2017)
The purpose of this study is to unpack computer aided teaching. It focuses on an exploration into the methods of using a computer as a teaching tool for ordinary level students in Shurugwi District Urban Cluster located in the Midlands Province. A multiple case study approach was used to gather relevant data required for the study. Three School Heads, three computer science teachers and six pupils from form three and four purposively participated in the study. The research attempted to achieve triangulation in data gathering instruments through incorporating interviews as the main instrument complemented by document analysis and non-participant observation. The data collected was critically analysed to find out the extent of computer aided teaching application in the classroom to teach ordinary level students. Research findings revealed that teachers are not fully embracing computer aided teaching to a greater extent mainly due to lack of adequate computer resources for use to apply computer aided teaching and lack of support from the school administrations to financially support the department with enough resources. Pupils interviewed indicated that they enjoyed learning using the computer and research has suggested the computer to be a good teaching aid. The study recommends that the Ministry of Primary and Secondary Education officials (computer studies subject inspectors) in particular must organize seminars and workshops to help alert the School Heads and other stakeholders (teachers and parents) on the importance of this new dispensation of computer aided teaching and that it can be applied to all other subjects of the school curriculum.